Intracranial ependymomas: molecular insights and translation to treatment. (12th September 2019) - Lester, Ashleigh; McDonald, Kerrie L.
Abstract: Ependymomas are primary central nervous system tumors (CNS), arising within the posterior fossa and supratentorial regions of the brain, and in the spine. Over the last decade, research has resulted in substantial insights into the molecular characteristics of ependymomas, and significant advances have been made in the establishment of a molecular classification system. Ependymomas both within and between the three CNS regions in which they arise, have been shown to contain distinct genetic, epigenetic and cytogenic aberrations, with at least three molecularly distinct subgroups identified within each region. However, these advances in molecular characterization have yet to be translated into clinical practice, with the standard treatment for ependymoma patients largely unchanged. This review summarizes the advances made in the molecular characterization of intracranial ependymomas, outlines the progress made in establishing preclinical models and proposes strategies for moving toward subgroup‐specific preclinical investigations and treatment.